On the boundary of the jumping spider genus Rhyphelia Simon, 1902 (Araneae: Salticidae: Euophryini), with description of ten new species - Nobre, Welington B.; Ruiz, Gustavo R.s. (Zootaxa, 2024)
In this paper we synonymize Soesilarishius Makhan, 2007 with Rhyphelia Simon, 1902. We give new illustrations of the male holotype of the type species Rhyphelia variegata Simon, 1902 for comparisons, and describe the closely related Rhyphelia brevistylus sp. nov. (♂♀) from the state of Bahia, Brazil. Additionally, we describe nine other new species from different Brazilian regions: Rhyphelia barbado sp. nov. (♂) from Bahia, Rhyphelia bilineata sp. nov. (♂♀) from Minas Gerais, Rhyphelia cotriguacuensis sp. nov. (♂) from Mato Grosso, Rhyphelia gallina sp. nov. (♂) from Acre, Rhyphelia novalima sp. nov. (♂♀) and Rhyphelia okay sp. nov. (♂♀) from Minas Gerais, Rhyphelia otti sp. nov. (♂♀) from Rio Grande do Sul, Rhyphelia planaria sp. nov. (♂) from São Paulo, and Rhyphelia tocantinensis sp. nov. (♂) from Tocantins.